PENGARUH PENAMBAHAN ADMIXTUREAIR ENTRAINING AGENT 0.04%,0.08%,0.12% PADA KUAT TEKAN BETON DENGAN MUTU fc 25 MPa - Aulia, Syafaril Hanif (Universitas Negeri Surabaya, 2023)
This study aims to determine the compressive strength of cylindrical concrete with fc' quality of 25 MPa with the addition of AEA additives. Based on the AEA brochure, this added material is a water-soluble polymer which functions to reduce the weight of concrete and reduce the use of cement in the mix. The concrete mix test was divided into three mixtures, namely with the addition of AEA 0.04%, 0.08% and 0.12% respectively by weight of cement. The composition of the concrete mix consists of 18.48 kg of cement, 46.9 kg of fine aggregate, 22.58 kg of aggregate and 5.98 kg of water. The compressive strength test results for cylindrical concrete with 0.04% AEA added at 28 days of age were 25.02 MPa. The compressive strength of cylindrical concrete with 0.08% AEA added at 28 days of age is 20.55 MPa. Furthermore, the compressive strength of cylindrical concrete with 0.12% AEA added material at 28 days of age is 17.4 MPa.